Safety of Rivaroxaban for Postoperative Venous Thromboembolism Prophylaxis Following Abdominal Body Contouring Surgery: 600 Patients. (24th June 2020) - Vasilakis, Vasileios; Kortesis, Bill G; Bharti, Gaurav; Isakson, Matthew H; Hunstad, Joseph P
Abstract: Background: Reducing the incidence of venous thromboembolism (VTE) following abdominal body contouring surgery remains a top priority for patient safety. There is a lack of consensus regarding the optimal chemoprophylactic agent for postoperative VTE prophylaxis, and the role of oral anticoagulants warrants further investigation. Objectives: The aim of this multisurgeon, single-institution study was to determine the safety and efficacy of a 7-day postoperative rivaroxaban regimen for VTE prophylaxis in abdominal body contouring surgery. Methods: A retrospective chart review was performed of all patients who underwent abdominoplasty, circumferential body lift, fleur-de-lis panniculectomy, or circumferential fleur-de-lis panniculectomy at our surgical center from August 2014 to November 2019. A 7-day postoperative course of once-daily 10 mg rivaroxaban, starting on postoperative day 1, was administered to every patient unless there was a contraindication. The 2 primary endpoints were the incidence of VTE and bleeding events. Results: A total of 600 patients were included in the study. There were no deaths. There were 4 (0.7%) incidents of VTE events: 2 (0.3%) patients suffered pulmonary embolus and 2 (0.3%) patients suffered a lower-extremity deep venous thrombosis. A total of 13 (2.2%) patients suffered complications related to bleeding. Of these, operative intervention for control and evacuation was required in 7 (1.2%) patients. Conclusions: A 7-day postoperative course of once-daily rivaroxaban for VTE risk reduction in abdominal body contouring surgery is associated with a low incidence of VTE events and a low risk of bleeding complications. Level of Evidence: 4: